High recovery water reclamation process - Neo, Puay Lin (2019)
Global water use has been increasing at a rapid rate due to population growth, and more areas are facing severe water scarcity. The conversion of wastewater into reusable water has been gaining attention as it is an important source of water. In water reclamation, reverse osmosis (RO) is the key technology in treating wastewater for reuse. However, membrane fouling by organics, inorganics and biological substances, has continuously hindered the membrane performance. Moreover, high RO recovery is necessary to increase the amount of product water. However, at high recovery, RO fouling is often exacerbated as the more concentrated retentate stream increases the fouling potential. Thus, the foulant compositions, fouling mechanisms and RO feed water quality at high recovery lab-scale RO processes were analysed in this study. The different types of RO feed water quality were obtained from pre-treatment with a novel nanofiltration-membrane bioreactor (NF-MBR) and an ultrafiltration-MBR (UF-MBR). The large increase in trans-membrane pressure (TMP) revealed the higher fouling rate was associated with high recovery as well as the lower feed water quality in terms of dissolved organic carbon (DOC) that was treated by UF-MBR. On the other hand, 90% RO recovery was achievable with the NF-MBR permeate which has lower DOC despite higher Ca & P content under the concentration factor effect. Results obtained showed that the combined effects of organic-inorganic fouling during high recovery RO processes could be observed as a dense fouling layer was formed with high amount of extracellular polymeric substances, ATP, Ca-P etc.